Chemical Treatments for Native Oxides Removal of GaAs Wafers. (11th September 2015) - Rebaud, Mickaël; Roure, Marie-Christine; Loup, Virginie; Rodriguez, Philippe; Martinez, Eugénie; Besson, Pascal
Abstract : Two months air-aged GaAs wafers were treated with different chemistries. The effect on oxide removal and surface morphology was studied by XPS and AFM. In order to propose a global sequence to put value-back into these old wafers, a rinsing step with different content of dissolved O2 was practiced after selected chemical treatments. Results show that all applied treatments (HCl, HF, NH4 OH and (NH4 )2 S) are efficient for removing the native oxide. The chemical composition of the obtained surfaces depend of the chemistry. Basic treatments are preferable to conserve a smooth surface. Without S-passivation, a significant oxide growth is observed even if surfaces were only exposed 30 minutes to air. Short descriptions of potential mechanisms occurring at surface are discussed.